Sistem Aplikasi Layanan Panggilan Montir Berbasis Web untuk Memudahkan Pengendara Menemukan Montir - Ratu Yuri Meissy (Informatics Study Program, Faculty of Engineering and Computers, Baturaja University, 2023)
The number of motorized vehicle riders has drastically increased, leading to a rise in problems such as breakdowns, flat tires, and broken chains while on the road. Especially for riders who are unfamiliar with the surrounding area, it can be challenging to find a nearby mechanic or garage. Therefore, Canic is a web-based application that provides on-demand mechanic services. The application enables riders to easily address vehicle issues by displaying a list of nearby mechanics based on the rider's location. The rider can then select the preferred mechanic and make a booking, with the mechanic coming to the rider's location. The application was designed using Figma, Visual Studio Code, PHP Native, and MySQL as a supporting applications. The application's main features aid riders in finding nearby mechanics and viewing detailed transaction records. Based on a survey of 36 respondents, the application can facilitate riders in finding nearby mechanics from their location. In conclusion, Canic offers a practical solution to address the problem of riders facing vehicle issues while on the road. By providing a user-friendly interface and reliable mechanic services, Canic can help riders avoid further inconvenience and continue their journey with ease.